Bound States of 2D Bosonic Oscillator in a Magnetic Field in Anti deSitter Space - Sek Lakhdar; Falek Mokhtar; Moumni Mustafa (ENSTA – Algiers, 2024)
We conduct an analytical investigation of the two-dimensional deformed bosonic oscillator equation, which describes the behavior of charged particles (both spin 0 and spin 1 particles) in the presence of a uniform magnetic field. This study takes into account a minimal uncertainty in momentum arising from the anti-de Sitter model. To solve the system, we employ the Nikiforov-Uvarov (NU) method. Our analysis yields exact energy eigenvalues and corresponding wave functions for scalar Duffin-Kemmer-Petiau (DKP) case. We observe that even for large principal quantum numbers, the deformed spectrum remains discrete. For the spin 1 DKP case, we elucidate the behavior of the DKP equation and determine the nonrelativistic energies. We demonstrate that the space deformation introduces a new spin-orbit interaction proportional to its parameter. الملخص: نجري دراسة تحليلية لمعادلة مهتز بوزوني مشوه ثنائي الأبعاد، التي تصف سلوك الجسيمات المشحونة (سواء كانت جسيمات ذات لف مغزلي 0 أو 1) تحت تأثير مجال مغناطيسي منتظم. تأخذ هذه الدراسة في الاعتبار حدًا أدنى من عدم اليقين في الزخم ناتج عن نموذج الفضاء المضاد دي سيتر. لحل النظام، نعتمد على طريقة نيكيفوروف-أوفاروف (NU). ينتج عن تحليلنا قيم ذاتية للطاقة ووظائف موجية دقيقة لحالة دافين-كيمر-بيتيان (DKP) للجسيمات السلمية. نلاحظ أنه حتى بالنسبة لأعداد الكم الرئيسية الكبيرة، يظل الطيف المشوه متقطعًا. بالنسبة لحالة DKP ذات اللف المغزلي 1، نوضح سلوك معادلة DKP ونحدد الطاقات غير النسبية. نبيّن أن تشوه الفضاء يُدخل تفاعلاً جديداً بين اللف المداري والنواة يتناسب مع معاملاته.
Intervention
Keywords: DKP equation; anti-de Sitter space; Scalar case; Vector case; Magnetic field; معادلة دوفين كيميرباتيوDKP; فضاء مضاد ديسيتر; حالة سلمية; حالة شعاعية; مجال مغناطيسي